Análise espacial e temporal dos óbitos maternos por pré-eclâmpsia no Brasil de 2009 a 2018 - Rodrigues, Ivana Rios (2021)
Preeclampsia (PE) is a multisystem disorder and represents one of the most serious complications that can occur during pregnancy. The general objective of the study was to identify the characteristics of deaths from preeclampsia in Brazil, from 2009 to 2018.National population-based ecological study, using secondary mortality data from the database of maternal deaths of the Department of Informatics of the Unified Health System in Brazil. Descriptive analysis, temporal trend analysis and spatial analysis were carried out. There were 22,039 maternal deaths recorded in Brazil, of which 3,493 (15.84%) were related to PE. The disease was mentioned as the underlying cause in 1,540 deaths (44.1%) and as an associated cause in 1,953 deaths (55.9%). In the age group from 10 to 49 years, there was an increase in standardized mortality coefficients as the underlying cause (AAPC: 8,2; IC 95%: 2,2 a 14,5; p<0,001). The analysis revealed growth in the Midwest (AAPC: 7.1; 95% CI: 1.1 to 14.5; p<0.001), Northeast (AAPC: 5.5; 95% CI: 5.1 to 5 .9; p<0.001), South (AAPC: 10.9; 95% CI: 2.4 to 20.4; p<0.001) and Southeast (AAPC: 9.1; 95% CI: 2.9 to 15 .7; p<0.001). As associated cause, the most affected age group was 15 to 19 years old (AAPC: 10.4; 95% CI: 1.1 to 20.6; p<0.001). There was a growing trend in the Northeast (AAPC: 7.9; 95% CI: 2.1 to 13.9; p<0.001) and Southeast (AAPC: 7.8; 95% CI: 1.1 to 14.9; p<0.001). When considering PE as the underlying cause, the spatial analysis indicated that 677 municipalities had at least one death, with the municipality with the highest mortality rate being Vila Nova do Sul (1789.27), in Rio Grande do Sul. However, when PE is considered as the underlying + associated cause, it can be seen that 902 municipalities had at least one death, with the highest coefficient being the municipality of Serranópolis de Minas (26.38), in Minas Gerais. High-risk clusters (High/High) covering areas of the North, Northeast, Southeast and Midwest were identified as the underlying cause and 22 municipalities had high mortality rates. As the underlying + associated cause, high risk clusters (High/High) were identified covering areas of all regions of the country and 19 municipalities had high mortality rates. The data indicated allowed a broader view of mortality related to PE in Brazil. Mortality coefficients showed an increasing trend. The process of spatial and temporal distribution confirm the thesis that deaths from PE in Brazil are associated with epidemiological, socioeconomic and health characteristics.